Cada um luta da sua trincheira: as estratégias para criação e compartilhamento de conteúdo de ativismos sociais no Facebook - Pereira, Daniele Prates (2018)
The research that we propose in this thesis starts from problems presented to us in microssocial exploratory research - in which the subjects participate in events or campaigns in the social networks, but still do not consider themselves activists and, when they participate, the sensitivity with the cause is a key factor. In order to understand how the contents of social activism move in the social network of Facebook, we begin to observe this space through our personal profile. The methodology used was a microssocial observation, starting from the personal profile in the social network of Facebook, selecting as corpus cases in which the users of the network interacted or created activist contents. The research problem was: in what way the contents of social activism appear on Facebook and what elements are significant for them to have visibility and to travel on that network? To construct this discussion, we present the networked society, mediated by information and communication technologies, as well as its relations of symbolic power (BOURDIEU, 1989) and soft power (NYE JR., 2012). We discuss the participation of the subjects in the social reality, especially in democratic orders that allow and guarantee that so the subjects can act. So, in a second moment, we present the conceptions of democracy that defined our discussion (TILY, 2013) related to communication and the public sphere (HABERMAS, 2011) and political agonies (MOUFFE, 2005). We then discuss social activism (JORDAN, 2002) and construct a mapping of strategies that our microssocial methodology made possible to ob- serve. We find some practices that have been reiterated, such as public consultations, undersigned, alternative media, collaboration in actions or events, protection of those involved in actions or events, fundraising, use of robots, obsolescence of public oblivion through hashtag campaigns or avatars, and the creation and dissemination of content. We realize that there is a negative view related to activism in social networks, which is often called 'couch activism', trying to point to a lethargy of social actors. However, we visualize in our research that the form of softativist action in Facebook is transgressive and seeks to change the social or symbolic reality As for the visibility of the contents, it was possible to raise some significant elements. The first element of the visibility logic was the scheduling, the second was the rhetoric of the media, or rhetorical square, and the third significant element for the visibility of the contents was the framing. Visibility limiters were perceived, such as algorithmic programming, false news, technical conflicts, and the need for super-nodes. As for the content dynamics, it was possible to verify two logics: playfulness and affection. The discussion that the thesis provided allowed us to define as challenges for Democracy in the reality of the connection: the need for public authorities to convalidate social networks as influencers of the political agenda; the overcoming of binary political antagonisms, the need to insert some traditional political actors in the political debate of the networks, or their integration with the actors who stand out there; the recognition of plural positions as legitimate and the construction of alterity as a repertoire of action by the collective actors, especially in the construction of contents. Still, some challenges will be faced, such as the subversion of network programming, deconstructing the desdemocracy of the algorithm, and overcoming the de-democracy of the self - influenced by the bubbles of position and conviction.